Data Mining-Based Analysis of Modern Chinese Medicine for the Treatment of Stable Angina Pectoris in Coronary Heart Disease. (28th February 2022) - Luo, Min; Hu, Yuying; Bai, Rong; Xu, Zongpei
Abstract : The aim of this study is to explore the clinical effects of Chinese medicine in the treatment of stable angina pectoris in coronary heart disease. Chinese medicine has multitarget, multilevel, and multilink effects in the treatment of coronary angina, which can significantly improve patients' symptoms. Its mechanism of action involves multiple levels such as regulating lipid metabolism, improving platelet function, antioxidant, and protecting endothelial function. The design was based on data mining to analyse the dosing pattern of modern Chinese medicine for the treatment of stable angina pectoris in coronary heart disease. The number of episodes of angina pectoris, the duration of the episodes, and the changes in the electrocardiogram before and after taking the medicine were observed and compared between the two groups. The number and duration of angina attacks ((2.23 ± 0.77) per week and (1.31 ± 0.34) min/time, respectively) in the study group were found to be significantly better than those in the control group ((3.86 ± 1.03) per week and (2.46 ± 1.21) min/time, respectively).